Low Birth Weight in Brazil Vulnerable Groups: An Analysis Based on Data Mining and Big Data - Cunha, José Gustavo; Lucas, Tarcísio Daniel Pontes; Lucas, Andreza Daniela Pontes; Ferreira, Monaliza de Oliveira (Anais da Brazilian Conference on Intelligent Systems (BRACIS), 2024)
Low Birth Weight (LBW) is the most important isolated risk factor for infant mortality. Several studies are conducted to understand the features related to the increased of LBW rate in Brazil. However, few works aggregate national and special vulnerable groups analysis. Furthermore, some data mining methodologies with potential to discover new information from datasets, such as subgroup discovery, have not yet been applied for this purpose. Thus, this study aims to identify and analysis features sets related to LBW in low-income families from Brazil and comparing them with six more vulnerable groups: small towns, rural areas, illiterate mothers, adolescent mothers, indigenous and quilombolas. We also development a dashboard for publicize features set related to LBW in several Brazilian cities.